Gender Performativity of Women in Responding to Gender Constructs Within the Student Activity Unit (UKM) of Pencak Silat at Unusia - Safitri, Erina; Maryaman, Liskawati; Anjani, Emilia; Khoirot, Rossa Umdatul; Maulana, Moh. Faiz (EGALITA, 2025)
Abstract This study examines the gender performativity of women in responding to patriarchal gender constructions within the Student Activity Unit (UKM) of Pencak Silat at Universitas Nahdlatul Ulama Indonesia (Unusia). Using Judith Butler’s theory of gender performativity, this qualitative case study explores how female athletes negotiate and challenge masculine stereotypes embedded in martial arts. Data were collected through participant observation, in-depth interviews, and documentation involving five female members of the UKM. The findings show that women perform gender through repetitive practices such as intensive training, mixed-gender sessions, and consistent athletic achievements, including competitive success that challenges assumptions of female physical inferiority. The supportive organizational environment of the UKM plays a crucial role in enabling these practices and strengthening women’s agency. This study contributes novelty by situating gender performativity within a campus-based martial arts organization, highlighting sport as a site of gender negotiation. Practically, the findings suggest that inclusive training systems in student organizations can foster gender equality and empower women in traditionally masculine spaces. Keywords: Gender Performativity; Gender Construction; Pencak Silat Abstrak Penelitian ini mengkaji performativitas gender perempuan dalam merespons konstruksi gender patriarkal di Unit Kegiatan Mahasiswa (UKM) Pencak Silat Universitas Nahdlatul Ulama Indonesia (Unusia). Dengan menggunakan teori performativitas gender Judith Butler, penelitian ini menganalisis bagaimana perempuan menegosiasikan dan menantang stereotip maskulinitas dalam olahraga bela diri. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus melalui observasi partisipatif, wawancara mendalam, dan dokumentasi terhadap lima anggota perempuan UKM. Hasil penelitian menunjukkan bahwa perempuan melakukan performativitas gender melalui praktik berulang seperti latihan intensif, latihan bersama atlet laki-laki, serta pencapaian prestasi kompetitif yang konsisten. Lingkungan UKM yang relatif inklusif berperan penting dalam memperkuat agensi dan kepercayaan diri atlet perempuan. Kebaruan penelitian ini terletak pada analisis performativitas gender dalam konteks organisasi mahasiswa berbasis olahraga bela diri. Secara praktis, temuan ini menunjukkan bahwa UKM dapat menjadi ruang strategis dalam mendorong kesetaraan gender di lingkungan kampus. Kata Kunci: Performativitas Gender; Konstruksi Gender; Pencak Silat